2013
DOI: 10.5603/ep.2013.0004
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of follicle stimulating hormone receptor (FSHR) in neuroendocrine tumours

Abstract: Introduction: Follicle stimulating hormone receptors (FSHR) are well known to be expressed in gonads and in gonadal tumours. Recently, their incidence has also been revealed in endocrine non-gonadal tumours such as adrenal and pituitary tumours. Moreover, FSHR immunostaining has also been reported in endothelium of intra-and peritumoral blood vessels of a large series of cancers. The present paper reports on the incidence of FSHR in both tumoral cells and some intratumoral blood vessels of neuroendocrine tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 8 publications
2
12
0
2
Order By: Relevance
“…In contrast, the non-tumoural blood vessels (with the exception of the vasculature in the reproductive organs and umbilical veins) do not contain FSHR protein. This observation was confirmed soon after by other authors [19,[51][52][53]. It seems reasonable to suppose that FSHR-positive blood vessels represent the vasculature formed through tumoral neo-angiogenesis, and like in their classical targets, i.e.…”
Section: The Role Of Gonadotropins In Neoplasiasupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast, the non-tumoural blood vessels (with the exception of the vasculature in the reproductive organs and umbilical veins) do not contain FSHR protein. This observation was confirmed soon after by other authors [19,[51][52][53]. It seems reasonable to suppose that FSHR-positive blood vessels represent the vasculature formed through tumoral neo-angiogenesis, and like in their classical targets, i.e.…”
Section: The Role Of Gonadotropins In Neoplasiasupporting
confidence: 58%
“…the reproductive organs, are involved in the neo-angiogenesis process [54]. FSHR were also demonstrated by means of immunohistochemistry in tumoural cells, mostly in tumours of endocrine origin [19,[51][52][53]55]. However, in contrast to the expression of FSHR in tumoural cells of the gonadal [18,56] and prostatic tumours [57,58], which is well established, their occurrence in tumoural cells beyond the reproductive system is still controversial.…”
Section: The Role Of Gonadotropins In Neoplasiamentioning
confidence: 99%
“…Recent studies have revealed the ectopic expression of follicle stimulating hormone receptors (FSHR) in the endothelium of intra-and peritumoural blood vessels of several human neoplasms [1][2][3][4]. Moreover, in some tumours, like adrenal tumours [2], thyroid cancers [4], neuroendocrine tumours [3,5], and soft tissue sarcomas [6], the expression of FSHR occurs also in tumoural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in some tumours, like adrenal tumours [2], thyroid cancers [4], neuroendocrine tumours [3,5], and soft tissue sarcomas [6], the expression of FSHR occurs also in tumoural cells. In our earlier study, we found also FSHR expression in the majority of pituitary adenomas [2].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing evidence to show that FSH receptors are expressed in many extragonadal tissues, such as fallopian tubes (Zheng, Magid, Kramer, & Chen, ), pituitary gland (Wang et al, ), urinary bladder and urethra (Ponglowhapan, Church, & Khalid, ), cervix (Leethongdee, Khalid, & Scaramuzzi, ), umbilical cord and placenta (Stilley, Christensen, et al, ). Follicle‐stimulating hormone receptor (FSHR) is also expressed in osteoclasts where FSH signalling mediates bone resorption (Zhu et al, ), and in neuroendocrine tumours (NETs) where its role has not yet been elucidated (Pawlikowski, Winczyk, & Stępień, ). Recently, LiangChen, Liu, and Zhou () demonstrated that FSHR expressed in the porcine uterus with differences according to the stage of the oestrous cycle.…”
Section: Introductionmentioning
confidence: 99%